Rhizobium sophorae strain 33504-Borg2 as a biocontrol agent to mitigate the impacts of cucumber mosaic virus infection in faba bean - Abdelkhalek, Ahmed; Hamzah, Karrar A.; Elbeaino, Toufic; Behiry, Said I.; Moawad, Hassan; Al-Askar, Abdulaziz A. (Frontiers in Plant Science, 2025)
The application of Rhizobium spp., nitrogen-fixing bacteria, as a biocontrol agent to improve resistance to plant viral infections signifies a promising approach for sustainable and eco-friendly agricultural practices. The current study evaluated the effectiveness of strain 33504-Borg2 of Rhizobium sophorae in promoting faba bean growth and enhancing its systemic defense response to cucumber mosaic virus (CMV). Under greenhouse conditions, the pre-treatment of soil with 33504-Borg2 resulted in significant improvements in plant growth, an increase in chlorophyll content, as well as a reduction in the incidence and severity of disease and CMV accumulation by 44%, 72.5%, and 71%, respectively. The application of 33504-Borg2 inoculation also demonstrated a reduction in non-enzymatic markers of oxidative stress, such as hydrogen peroxide and malondialdehyde, alongside a notable increase in enzymes that mitigate reactive oxygen species, including polyphenol oxidase and peroxidase. Moreover, the expression levels of some genes associated with defense mechanisms, including pathogenesis-related proteins and those involved in the polyphenolic pathway, showed a notable increase. The HPLC analysis indicated that plants treated with 33504-Borg2 exhibited increased accumulation of numerous polyphenolic compounds, including gallic acid, ellagic acid, coumaric acid, pyrocatechol, and catechin. Hence, the capacity 33504-Borg2 to promote plant growth and enhance systemic resistance to CMV encourages its application as a biocontrol and biofertilizer agent. This application offers an innovative approach to protecting plants, promoting sustainability, and guaranteeing agricultural environmental security. To the best of our knowledge, this study represents the first investigation of R. sophorae as a biocontrol agent against CMV infestation.